2002
DOI: 10.1152/ajpgi.00080.2002
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen blocks LES relaxation and crural diaphragm inhibition by esophageal and gastric distension in cats

Abstract: Recent studies indicate that baclofen decreases the frequency of TLESR; however, its effect on the crural diaphragm is not known. We evaluated the effects of baclofen on LES relaxation and crural diaphragm inhibition induced by gastric distension and esophageal distension in cats. Five adult cats underwent surgical implantation of wire electrodes into the crural and costal diaphragm for measurement of their EMG activity, respectively. One week after the surgery, animals were lightly sedated and recordings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Contraction of the CD is likely to be important. We found that LES tone returned between phases C and D of descent of the GEJ and this is consistent with contraction of the CD which forms the extrinsic LES 23–26 …”
Section: Discussionsupporting
confidence: 81%
“…Contraction of the CD is likely to be important. We found that LES tone returned between phases C and D of descent of the GEJ and this is consistent with contraction of the CD which forms the extrinsic LES 23–26 …”
Section: Discussionsupporting
confidence: 81%
“…54 Studies assessing the effects of GABA-B agonists on crural diaphragm relaxation are limited, but it has been demonstrated that GABA-B agonists block the reflex inhibitory pathway to both LOS and crural diaphragm in cats. 56 This finding could theoretically be caused by the fact that LOS and crural diaphragm relaxation share pathways. 47 …”
Section: Gaba-bmentioning
confidence: 99%
“…Furthermore, as shown in the present work, displacement of [ 3 H]‐GABA from dog and rat brain membranes was almost identical for most agonists tested. Previous work has shown that baclofen has, at comparable doses, very similar potency in dogs (Lehmann et al ., 1999), ferrets (Blackshaw et al ., 1999), cats (Liu et al ., 2002) and humans (Lidums et al ., 2000; Zhang et al ., 2002) as an inhibitor of TLOSRs. In addition, lesogaberan has similar effects on TLOSR in dogs and humans at comparable plasma exposures (Lehmann et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%